2017
DOI: 10.1002/ijc.30868
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and TWIST1 in a 16‐biomarker immunoprofile useful for prognosis of breast cancer patients

Abstract: This study concerns the expression of biomarkers involved in diverse pathways, such as progression, DNA repair mechanisms and angiogenesis to establish an immunoprofile capable of characterizing sporadic versus familial breast cancers (BCs). The aim was to identify a patient subgroup with a different clinical outcome, which could then be directed towards new targeted therapies. Hierarchical cluster analysis (HCA) was carried out using the immunohistochemical score from tissue microarray sections of an initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In this study, a panel of factors involved in TME changes such as VEGF, VEGFR1, HIF-1a, TWIST1 and MVD, that have been related to BC progression, aggressiveness and invasion was analyzed [ 6 , 12 , 28 30 ]. Further, so as to better characterize this microenvironment, their association with the scaffolding protein NHERF1 and with survival was observed, allowing to identify a possible subgroup of patients that could benefit from a specific therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a panel of factors involved in TME changes such as VEGF, VEGFR1, HIF-1a, TWIST1 and MVD, that have been related to BC progression, aggressiveness and invasion was analyzed [ 6 , 12 , 28 30 ]. Further, so as to better characterize this microenvironment, their association with the scaffolding protein NHERF1 and with survival was observed, allowing to identify a possible subgroup of patients that could benefit from a specific therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As the results showed that, the mechanism might be implicated in several biological processes and signaling pathways, such as DNA damage and repair, transcription and translation process, post‐translation protein modification, cell cycle, carcinogensis genes and pathways ( KARS , EGFR , VEGF , WNT pathway, Hedgehog pathway). It is important to note that the above biological processes and pathways are significantly associated with cancer prognosis . A number of studies have demonstrated the involvement of several of these processes in pancreatic cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the above biological processes and pathways are significantly associated with cancer prognosis. [67][68][69][70][71][72][73][74][75] A number of studies have demonstrated the involvement of several of these processes in pancreatic cancer prognosis. For example, the low expression of CHD5 could activate DNA damage response and function as useful biomarker for pancreatic cancer poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the development of other anti-VEGF-VEGFR drugs such as VEGF-Trap and humanized anti-VEGFR antibodies is consistently ongoing to overcome adverse drug effects. Recent studies suggest that VEGF pathway appears to be useful for prognosis of several cancers patients including breast cancer and is also conducted as the most critical pathway regulating liver and lymph node metastasis of breast cancer ( 60 62 ). Therefore, we can use VEGF-VEGFR system as a potential target of new drugs, and more detailed structure-based insightful information regarding the VEGF-VEGFR system is essential to improve the anti-angiogenic therapy for the improved quality of life of cancer patients.…”
Section: Angiogenesis and Anti-angiogenic Therapy In Cancermentioning
confidence: 99%